Growth of Roots and Rhizomes in Two Desert Grasses as Influenced by Defoliation Stress and Nitrogen Application - Kathju, S; Shankarnarayan, K A; Vyas, S P; Lahiri, A N (Annals of Arid Zone, 2016)
- Â